The Fanconi Anemia Pathway in Cancer - Niraj, Joshi (Annu Rev Cancer Biol, 2018)
Fanconi anemia (FA) is a complex genetic disorder characterized by bone marrow failure (BMF), congenital defects, inability to repair DNA interstrand cross-links (ICLs), and cancer predisposition. FA presents two seemingly opposite characteristics: (a) massive cell death of the hematopoietic stem and progenitor cell (HSPC) compartment due to extensive genomic instability, leading to BMF, and (b) uncontrolled cell proliferation leading to FA-associated malignancies. The canonical function of the FA proteins is to collaborate with several other DNA repair proteins to eliminate clastogenic (chromosome-breaking) effects of DNA ICLs. Recent discoveries reveal that the FA pathway functions in a critical tumor-suppressor network to preserve genomic integrity by stabilizing replication forks, mitigating replication stress, and regulating cytokinesis. Homozygous germline mutations (biallelic) in 22 FANC genes cause FA, whereas heterozygous germline mutations in some of the FANC genes (monoallelic), such as BRCA1 and BRCA2, do not cause FA but significantly increase cancer susceptibility sporadically in the general population. In this review, we discuss our current understanding of the functions of the FA pathway in the maintenance of genomic stability, and we present an overview of the prevalence and clinical relevance of somatic mutations in FA genes.